A Case study on changing education paradigms driven in topsy turvey situation of covid 19 (Trinity Journal of Management, IT & Media (TJMITM), 2022)
The impact of the COVID-19 pandemic on education is vast, ranging from the adoption ofonline classes to better understanding the nature of the rapid institutional transition duringthe pandemic situation.The pandemic has resulted in reduced academic attainment andunfinished learning, which had a profound effect on the future economic prospects ofmillennials. In fact, the pandemic had shown the potential to thwart the plans of manymillennials to go to college and find a rewarding career to support themselves and theirfamilies. While the effects were diverse, the cumulative cost of unfinished learning andachievement gaps were greater than the current investments made. But, the sudden shift ininstitutional teaching methodologies and conditions created around the education industrycreated the dilemmas about the results that will be demonstrated by the two groups ofuniversity faculty, separately identified as novice online teachers and expert online teachers.This case study aims to provide useful accounts of the changes that occurred ininterconnected teaching activity systems at the university while adopting online teaching,highlighting the complex factors underpinning individual academics’ experiences. The casestudy focuses on a ‘deep dive’ into the challenges faced by teachers in conductingdistance-learning activities while schools were closed.Finally, the case study presents lessons learned and recommendations on how to strengthensystems to provide a stronger education sector to bridge the gap between the reality andambitions of India’s education policy.
Keywords: Pandemic; Human; COVID-19; Cirus